Philosophical Values in the Motif Design of the Donggala Woven Fabric - Dwi Septiwiharti; Haliadi; Anjar Kusuma Dewi (Universitas Airlangga, 2025)
The Donggala woven fabric is characterized by a wide range of motif designs that are influenced by the community’s depictions of their own identity and the environment, including both nature and culture. This influence is evident in the designs’ substance, which showcases a fusion of the Kaili community’s culture and natural beauty in Central Sulawesi. The objective of this study is to comprehend the philosophical principles that are reflected in the motif designs of Donggala woven fabric and to offer a comprehensive account of the evolution of human thought within the culture that supports it. This study implemented a philosophical method that is supplemented by a historical method. Hermeneutics and van Peursen’s cultural philosophy are employed as the philosophical analysis method. The results indicate that the meanings embedded in the motif designs of Donggala woven fabric are representative of the evolution of the Kaili ethnic community’s perspective on themselves, others, the universe, and the dimension of religiosity. The motif patterns of Donggala woven fabric are designed from this perspective. The characteristics of Donggala woven fabric motif designs are influenced by mythical, ontological, and functional modes of thought from a philosophical perspective. Donggala woven fabric is distinguished by its consistent use of the fundamental motif of buya bomba or floral patterns. A diversity of decorative patterns that have been preserved to this day are represented by this fundamental motif. It demonstrates that the Kaili community is consistently focused on the natural environment as the foundation of their thought and behavior, which is reflected in the ecological characteristics of the Donggala woven fabric motif designs.